UPAYA DAN HAMBATAN PEMENUHAN HAK DAN KEWAJIBAN PESERTA BPJS KETENAGAKERJAAN DI DESA OESENA, KECAMATAN MIOMAFFO TIMUR, KABUPATEN TIMOR TENGAH UTARA - Ketmoen, Hendrikus Natanael; Aloysius, Sukardan; Jacob, Yossie M Y (Petitum Law Journal, 2023)
BPJS Ketenagakerjaan participants who are workers are entitled to legal protection, because it is included in the National Social Security System and is a state program with the aim of providing certainty of protection and social welfare for all Indonesian people. Legal protection has the purpose of providing protection to human rights that are harmed by other individuals. Legal protection is a variety of legal efforts that must be given by law enforcement officers in order to form a sense of security, either physically or mentally from various threats from any party and given to the community so that they can enjoy all the rights granted by law. This study is included in Empirical Legal Research is a method of legal research that seeks to see the law in a real sense or can be said to see, examine how the law works in society, which then uses a research approach, a type of qualitative approach. Efforts to overcome the fulfillment of the rights and obligations of BPJS Ketenagakerjaan participants and obstacles in the fulfillment of the rights and obligations of BPJS ketenagakerjaan participants. The results showed that: (1) in Oesena Village, efforts to fulfill the rights and obligations of BPJS Ketenagakerjaan participants have been implemented but not maximally in accordance with the vision and mission of BPJS Ketenagakerjaan, this can be seen from the difficulty of the BPJS Ketenagerjaan claim process for work accident insurance. Then, the disbursement of Old-Age Security for participants who die or experience permanent disability should be able to take place more quickly because it is urgent, and many participants do not understand their rights as BPJS Ketenagakerjaan participants due to lack of socialization. (2) There are several factors that become obstacles in fulfilling the rights and obligations of BPJS Ketenagakerjaan participants, namely internal factors and external factors.